Lessons from the operation of the 'Penning-Fluorescent' TPC and prospects. (October 2015) - Gonzalez-Diaz, Diego; Aznar, F; Castel, J; Cebrián, S; Dafni, T; García, J A; Garza, J G; Gómez, H; Herrera, D C; Iguaz, F J; Irastorza, I G; Lagraba, A; et al.
Abstract: We have recently reported the development of a new type of high-pressure Xenon time projection chamber operated with an ultra-low diffusion mixture and that simultaneously displays Penning effect and fluorescence in the near-visible region (300 nm). The concept, dubbed 'Penning-Fluorescent' TPC, allows the simultaneous reconstruction of primary charge and scintillation with high topological and calorimetric fidelity.